A questionnaire based cross sectional survey of attitude and practice of complementary and alternative medicine in medical practitioners - Pradnya Deolekar; Kavitha Dongerkery; Pramila Yadav; Swati Sonawane (Al Ameen Medical College, 2022)
Background: Complementary and alternative medicine (CAM) has been practised in India since many years. People unsatisﬁed with conventional medicine often turn to unconventional alternatives. Aim is to appraise the extent of use of CAM amongst doctors and to examine their perception, attitude and practice towards CAM. Methods: This study was conducted among 105 doctors. A predesigned validated, questionnaire was used to evaluate the attitude and practice. Of 150 physicians who were given questionnaire to participate in the survey, 105 (70%) responded. Results: 22 (20.95%) were specialists and 83 (79.04%) General physicians. 79 (75.23%) Physician's considered that CAM has a beneficial role and 69 (65.71%) advised use of CAM in patients but only 25.71% would refer patients to CAM practitioners for treatment of an ailment. Of the total 105 physicians 31.42%. General practitioners suggested Ayurveda therapy as compared to 10.47% specialists. 36% of the patients preferred Ayurveda as opined by the physician. Homeopathy was recommended by 35% followed by herbal medicine 32% and 30% naturopathy. However, physicians' responses on most of the CAM therapies i.e. Ayurveda, homeopathy, naturopathy, herbal medicine etc. was found to be statistically not significant. Conclusions: In the future, physicians can more readily used CAM. Because evidence for the effectiveness of CAM remains sparse, more research is needed for the prudent use of CAM. An education and training system for potential CAM providers remains to be developed.